2002
DOI: 10.1007/s00221-002-1002-3
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular control of sympathetic activity

Abstract: It has been proposed that a vestibular reflex originating in the otolith organs and other body graviceptors modulates sympathetic activity during changes in posture with regard to gravity. To test this hypothesis, we selectively stimulated otolith and body graviceptors sinusoidally along different head axes in the coronal plane with off-vertical axis rotation (OVAR) and recorded sympathetic efferent activity in the peroneal nerve (muscle sympathetic nerve activity, MSNA), blood pressure, heart rate, and respir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
41
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(49 citation statements)
references
References 16 publications
6
41
0
Order By: Relevance
“…In humans, caloric vestibular stimulation (Cui et al, 1997) and head pitch (Ray and Carter, 2003), as well as GVS (Bent et al, 2006; Grewal et al, 2009; James and Macefield, 2010) influence SNA. Similarly, activation of the otolith organs using OVAR produces an increase in muscle SNA in-phase with the head-up tilt component and a decrease corresponding to the head-down component (Kaufmann et al, 2002). Moreover, linear acceleration (which specifically stimulates the otolith organs) causes transient changes in blood pressure (Cui et al, 1999) that are attenuated in patients with bilateral vestibular deficits (Yates et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…In humans, caloric vestibular stimulation (Cui et al, 1997) and head pitch (Ray and Carter, 2003), as well as GVS (Bent et al, 2006; Grewal et al, 2009; James and Macefield, 2010) influence SNA. Similarly, activation of the otolith organs using OVAR produces an increase in muscle SNA in-phase with the head-up tilt component and a decrease corresponding to the head-down component (Kaufmann et al, 2002). Moreover, linear acceleration (which specifically stimulates the otolith organs) causes transient changes in blood pressure (Cui et al, 1999) that are attenuated in patients with bilateral vestibular deficits (Yates et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The sinusoidal galvanic vestibular stimulation (sGVS) was generated by a computer-controlled stimulator (3234, 41, 42). Currents were delivered via sub-dermal needle electrodes placed in the skin over the mastoids.…”
Section: Methodsmentioning
confidence: 99%
“…Studies of neuro-vestibular function both during and after spaceflight have demonstrated abnormal otolith-ocular reflexes and spatial perception both during adaptation to microgravity as well as re-adaptation after return to Earth (8). In addition to its well-established role in spatial orientation, gaze control, and neuromotor function, recent work has demonstrated the presence of vestibulo-autonomic reflexes (32, 33, 36, 56, 57, 66). These excitatory vestibulo-autonomic reflexes are the earliest stimulation of sympathetic activity in response to changes of body position.…”
Section: Mechanisms Of Altered Autonomic Function In Spacementioning
confidence: 99%